Curricular trends in Malaysian medical schools: innovations within - Mohd Adnan, Nor Azila; Jaafar, Rogayah; Mohd Hussin, Zabidi Azhar (Academy of Medicine, Singapore, 2006)
INTRODUCTION: Various curricular innovations were adopted by medical schools worldwide in an attempt to produce medical graduates that could meet future healthcare needs of society locally and globally. This paper presents findings on curricular approaches implemented in Malaysian medical schools, in trying to meet those needs.